Finding a turn in Canadian management through archival sources. Issue 4 (11th November 2019) - Russell, Jason
Abstract : Purpose: The purpose of this paper is to reveal something about a turn that occurred in Canadian management from the 1960s to 1980s through an empirical analysis of three different archival research sources. It considers three sub-themes that collectively help to reveal empirically major changes in management identity that happened in Canada from the late 1960s to the early 1980s. Design/methodology/approach: This paper is divided into several sub-sections and uses social history methodology, although it is principally intended to be an empirical analysis. The rationale for selecting three specific sources and how they relate to each other is discussed. The sources are different in terms of form and periodization, yet they collectively provide coherent insights into the management experience in Canada from the 1960s to 1980s. Findings: As a methodology paper, this analysis reveals the unique nature of archival sources that are not often found in management history and also shows how they relate to each other. Research limitations/implications: This paper may seem specific to Canadian management history, but it is intended to present sources and methodology that are applicable regardless of locale. Originality/value: This paper seeks to present the value of using new methodologies in the study of management history and, while building on existing literature, it helps to reveal the complexity of the management experience in important decades in post-Second World War Canada.